The transcription factor Jun is necessary for optic nerve regeneration in larval zebrafish. - Sarah C Sarich; Virinchipuram S Sreevidya; Ava J Udvadia; Kurt R Svoboda; Jennifer H Gutzman (PLoS ONE)
Damage to the axons of the adult mammalian central nervous system (CNS) from traumatic injury or neurodegenerative diseases often results in permanent loss of function due to failure of axons to regenerate. Zebrafish, however, can express regeneration-associated genes to revert CNS neurons to a growth-competent state and regenerate damaged axons to functionality. An established model for CNS axon regeneration is optic nerve injury in zebrafish, where it was previously shown that thousands of genes are temporally expressed during the regeneration time course. It is likely that hubs of key transcription factors, rather than individual factors regulate the temporal clusters of expression after injury to facilitate cell survival, regrowth, and synaptic targeting in the brain. One transcription factor of interest in orchestrating CNS axon regeneration is jun. However, it remains unclear if CNS regeneration can progress without Jun. To test this, a transgenic zebrafish line was developed to express a heat-shock inducible dominant negative Jun. Induction of dominant negative Jun downregulated endogenous jun expression and larvae with functional jun knockdown demonstrated impaired retinal ganglion cell axon regeneration. Analysis of select putative Jun target genes, previously shown to be upregulated in adult zebrafish optic nerve regeneration, demonstrated that with functional Jun knockdown, atf3 and ascl1a were significantly downregulated, and sox11a was upregulated at distinct time points. These results position jun as a key regulator for successful optic nerve regeneration, further distinguish the regeneration program from development, and advance our knowledge for the formation of future therapies to treat CNS damage.